Analisis Yuridis Wanprestasi Oleh Penjual Dalam Jual Beli Melalui Media Internet - DHEA CYNARA TORONG (Jurnal Perspektif Hukum, 2021)
Agreement has become daily activity in trade. Online sale and purchase agreement is made on trust from one with another, so the agreement is made electronically using either email or other method; thus, there is not any document like in conventional sale and purchase transactions. The trading transactions in e-commerce system enables a seller to make transactions without having to directly meet (face to face) buyers/ consumers. Concerning the regulations on e-commerce, it uses the provisions in the third code and the provisions on e-commerce in the Civil Code with modification that e-commerce has special properties because it dominantly uses media and electronic devices. The research problems are whether the regulations on online sale and purchase transactions in the contract law in Indonesia have provided legal certainty to the contractual relationships between all parties involved in the transactions using internet media, how about the legal protection for any injured party due to default by sellers in the sale and purchase transaction using internet media, and how about the settlement to the consequences of default for all parties in the implementation of sale and purchase using internet media. This is an empirical juridical research. It is analytically descriptive which describes, explains and analyzes the problems, and find answers to the problems. This research employs library research and qualitative data analysis. It conducts interviews to collect data to the staff at Information Technology Department, in the Search & Business Analytic Division on blibli.com that have capacity as informants and information sources. The results demonstrate that e-commerce is principally done in the same way with conventional sale and purchase as regulated in Article 1320 of the Civil Code containing validating requirements of agreements based on the agreements between buyers and sellers or marketplace. The rights of buyers are guaranteed by sellers’ responsibility who defaults by indemnifying the costs such as: refund, return, or replacement. It is in line with the provisions stipulated in Article 1243 of the Civil Code; in which, when a seller defaults, the debtor shall pay for compensation. Any consequences due to default by seller in marketplace blibli.com is settled in accordance with the provisions stipulated in the trading contract of blibli.com as listed on the homepage of blibli.com. such as compensation in form of money or goods; the buyer, in demanding rights over default, has to comply with the provisions of blibli and provides evidence to blibli.com.